Apathy in Alzheimer's disease. (August 2018) - Nobis, Lisa; Husain, Masud
Highlights: Apathy is the commonest neuropsychiatric symptom in Alzheimer's disease (AD). Neuroimaging findings implicate frontostriatal circuits involving the anterior cingulate cortex. But the results are variable and interpretation is difficult for several reasons. Future studies might benefit from dissection of underlying behavioural mechanisms. Abstract : Apathy is the most common neuropsychiatric symptom in patients with Alzheimer's disease (AD). The presence of apathy has been related to greater caregiver distress, decreased quality of life, and increased morbidity. Here we review the most recent studies on this neuropsychiatric syndrome, focusing on prevalence, impact on quality of life, behavioural and neuroimaging studies, and treatment options. The results of some investigations on the behavioural and neuroanatomical profile of apathy in AD point to a role of frontostriatal circuits, specifically involving the anterior cingulate cortex. However, small and heterogeneous samples, lack of control for disease severity, and non-specific apathy scales complicate interpretation of results. Future studies might benefit from studying multiple dimensions of apathy within conceptual frameworks which allow for a deconstruction of underlying mechanisms.